Circulating Tfh cells and Tfr cells in papillary thyroid carcinoma and their diagnostic potential - Heng Zhang; Yiwen Yu; Minglei Jiang; Renquan Lu; Lin Guo (Immunobiology)
Objective: This study aim to explore the alterations of circulating T follicular helper (Tfh) and T follicular regulatory (Tfr) cells in the peripheral blood of patients with papillary thyroid carcinoma (PTC), assess their association with PTC and the influence on B cells, and evaluate their diagnostic potential. Methods: Peripheral blood samples were collected from 76 newly diagnosed PTC patients and 21 matched healthy controls between June 2023 and June 2024. Flow cytometry was used to determine the proportions of circulating Tfh and Tfr cells. The relationships between these cell populations and variables such as sex, age, and disease stage were analyzed. The diagnostic performance of circulating Tfh and Tfr cells, individually and in combination, was assessed using receiver operating characteristic (ROC) curves. Results: Compared to healthy controls, PTC patients exhibited an increased proportion of circulating Tfh cells and a decrease proportion of Tfr cells. While the increase in Tfh cells was not subtype-specific, the proportions of Th1-like and Th17-like Tfr subtypes were significantly altered in the PTC group. The proportion of Tfr cells remained unaffected by sex or age, whereas the increase in Tfh cells was more pronounced in male and elderly patients. Although no significant differences were observed across disease stages, changes in Tfh and Tfr cell proportions correlated with B cell subtypes and certain thyroid-related indicators. ROC plots showed circulating Tfr cells had higher sensitivity and specificity for distinguishing PTC compared to Tfh cells or their combination. Conclusion: PTC patients showed changed circulating Tfh cells and Tfr cells, presenting diagnostic potential.